A ANALISIS KECENDERUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DASAR NEGERI DI KABUPATEN GROBOGAN BERDASARKAN MULTIFACTOR LEADERSHIP QUESTIONNAIRE (MLQ) - Anna Rosyadah; Yari Dwikurnaningsih; Herry Sanoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
School leadership plays an important role in determining the effectiveness of school management and the achievement of educational goals. The leadership style applied by principals can influence teacher performance, work motivation, and the overall organizational climate in schools. Therefore, this study aims to analyze the tendency of leadership styles of principals in public elementary schools based on the Multifactor Leadership Questionnaire (MLQ). This research used a descriptive quantitative approach. The study was conducted in two public elementary schools located in Gubug District, Grobogan Regency, Central Java, involving two principals as research respondents. The respondents were selected purposively considering their role as the main leaders in school management. Data were collected using the MLQ instrument which measures three leadership dimensions: transformational leadership, transactional leadership, and passive (laissez-faire) leadership. The data were analyzed using descriptive analysis by calculating the total score for each leadership dimension. The results of the study indicate that the principals tend to apply a combination of transformational and transactional leadership styles. Both leadership dimensions obtained relatively high scores, while the passive leadership dimension showed very low scores. These findings indicate that the principals demonstrate active leadership practices in managing school organizations through structured work management as well as providing inspiration and direction to teachers. Thus, the combination of transformational and transactional leadership styles can support more effective school management and contribute to improving the quality of education.